Risk of amyotrophic lateral sclerosis and exposure to particulate matter: A case-control study. (30th September 2020) - Filippini, T; Mandrioli, J; Malagoli, C; Cherubini, A; Maffeis, G; Vinceti, M
Abstract: Background: Amyotrophic lateral sclerosis (ALS) is fatal neurodegenerative disease with still unknown etiology. Some environmental and occupational risk factors have been proposed, including air pollution, as suggested by recent studies. We carried out a case-control study in order to assess ALS risk due to environmental exposure to particulate matter ≤10 µm (PM10). Methods: We recruited ALS patients referred to the Modena Neurology Unit between 1994-2015 and a reference group sampled from the population of Modena province. Using a geographical information system-based dispersion model, we estimated outdoor air PM10 levels at the geocoded subjects' addresses of residence at the time of diagnosis. We computed odds ratio (OR) and 95% confidence interval (CI) of ALS according to increasing PM10 exposure, using an unconditional logistic regression model adjusted for age and sex. Results: For the study 132 participants (52 cases/80 controls), mean of annual average and maximum PM10 levels were 5.2 and 38.6 µg/m3, respectively. Using fixed cutpoints at 5, 10 and 20 of average annual PM10 levels, compared with subjects <5 µg/m3, we did not find an excess ALS risk associated with PM10 exposure, since OR was 0.87 (95%CI 0.39-1.96), 0.94 (0.24-3.70), and 0.87 (0.05-15.01) at 5-10, 10-20 and ≥20 µg/m3, respectively. When using maximum annual PM10 levels, we found an excess ALS risk for subjects exposed at 10-20 µg/m3 (OR = 4.27, 0.69-26.51) compared with exposure below 10 µg/m3. However, risk decreased with further exposure increase at 20-50 (OR = 1.49, 0.39-5.75), and ≥50 µg/m3 (OR = 1.16, 0.98-4.82). Conclusions: Our findings do not suggest that PM10 exposure is associated with ALS risk, even at the high levels of exposure characterizing a Northern Italy province. However, the statistically imprecise increased risks associated with maximum annual exposure levels suggest the need of further investigations. Key messages: Outdoor particulate matter exposure seems not associated risk of amyotrophic lateral sclerosis. Only exposure to high concentrations of particulate matter might increase risk of amyotrophic lateral sclerosis.